EFFECT OF TECHNOLOGY INTEGRATION IN ENHANCING CREATIVE THINKING AND INNOVATION AMONG SENIOR SECONDARY SCHOOL STUDENTS IN OWERRI MUNICIPAL, IMO STATE - Nwokorie, Chidimma Odochi (African Journal of Social and Behavioural Sciences, 2025)
This study investigated the Effect of Technology Integration in Enhancing Creative Thinking and Innovation among Senior Secondary School Students inOwerri Municipal, Imo State, with specific objectives of examining the effect of access to digital devices on students’ flexibility in thinking, investigating the influence of student exposure to digital platforms on their problem-solving ability, and assessing the impact of technology integration in lesson delivery on the level of student innovation projects. The study adopted a descriptive survey research design, with a population comprising all SSI–SS3 students in Owerri Municipal, from which a sample size of 400 students was determined using Taro Yamane’s formula. Five schools were sampled: Government Secondary School Owerri (GSSO), Owerri Girls Secondary School (OGSS), Urban Secondary School Owerri, Baptist High School Owerri, and FMC Staff Secondary School Owerri. Data were collected using a structured four-point Likert-scale questionnaire distributed to 400 students, of whom 387 were returned and 381 validated for analysis. Mean and standard deviation were employed to answer the research questions, while the hypotheses were tested using Multivariate Analysis of Covariance (MANCOVA). Findings revealed that access to digital devices significantly enhanced students’ flexibility in thinking, with Wilks’ Lambda = 0.873, F(4,376) = 15.294, p < 0.05, Partial Eta Squared = 0.140, showing that 14% of the variance in flexibility was explained by digital access. Similarly, exposure to digital platforms significantly influenced problem-solving ability with Wilks’ Lambda = 0.861, F(4,376) = 17.208, p < 0.05, Partial Eta Squared = 0.155, indicating 15.5% variance contribution. The integration of technology in lesson delivery significantly improved innovation projects, with Wilks’ Lambda = 0.849, F(4,376) = 18.734, p < 0.05, Partial Eta Squared = 0.166, explaining 16.6% of the variance. The study concluded that technology integration strongly enhances flexibility, problem-solving, and innovation among secondary school students, aligning with global educational demands. It was recommended that government, administrators, and teachers invest in digital infrastructure, training, and resources to foster creativity and innovation in schools.